Cell-Derived Nanoparticles are Endogenous Modulators of Sepsis With Therapeutic Potential. Issue 3 (September 2017) - Kunz, Natalia; Xia, Brent T.; Kalies, Kai-Uwe; Klinger, Matthias; Gemoll, Timo; Habermann, Jens K.; Whitacre, Brynne E.; Seitz, Aaron P.; Kalies, Kathrin; Caldwell, Charles C.
Abstract : ABSTRACT: Cell-derived nanoparticles (CDNPs) containing cytosolic proteins and RNAs/DNAs can be isolated from stressed eukaryotic cells. Previously, CDNPs isolated from cultured cells exerted immunomodulatory activities in different infections. Here, we sought to elucidate the role of CDNPs using a murine model of cecal ligation and puncture (CLP). We hypothesized that CDNPs influence the immune response at the site of infection, where severe cellular stress occurs. We observed early CDNP accumulation in the peritoneum after 4 h and continued CDNP presence 24 h after CLP. To determine whether CDNPs influence the host response to sepsis, we isolated CDNPs from a murine fibroblast cell line stressed by nutrient-deprivation, and injected them into septic mice. CDNP-treated mice demonstrated decreased peritoneal interleukin 6 levels and an approximately 2-log lower bacterial load compared with control mice 24 h after CLP. Additionally, a 20% CFU reduction was observed when incubating CDNPs with Pseudomona aeroginosa, indicating that CDNPs are bactericidal. To identify CDNP-responsive cells, CFSE-labeled CDNPs were injected into mice at the time of CLP. We observed that CDNPs were preferentially ingested by F4/80 + macrophages, and to a lesser degree, associated with inflammatory monocytes and neutrophils. Strikingly, CDNP-ingesting cells demonstrated elevated CD11b and MHCII expression compared with control cells. Altogether, our data indicate that CDNPs enhance the immune response at the site of infection and promote bacterial clearance, by direct bacterial killing and increasing phagocyte activation. Thus, CDNPs represent a novel, unexplored endogenous sepsis modulator with therapeutic potential. Abstract : Supplemental Digital Content is available in the text